The impact of the COVID-19 pandemic on the mood and family relationships of runners - Vilaregut, Anna; Abadia, Sixte; Pineda-Hernández, Sònia; Torras, Sònia; Pujadas, Xavier (Frontiers in Psychology, 2024)
The aim of this study was to analyze the impact of the COVID-19 lockdown on the mood of amateur runners and on their relationships with their partners and families. Adult runners 18 years or older (N=260) completed an online survey that included demographic information, standardized psychological assessments of Exercise Dependence (EDS-R) and mood (POMS), and, to measure relationship functioning, either the Dyadic Adjustment Scale (DAS) if they did not have children, or the Basic Family Evaluation Questionnaire (CERFB), measuring conjugal and parental relationships. Participants also answered questions about their exercise habits and the coping strategies they adopted during lockdown. The results suggest that runners who saw the largest reductions in time spent exercising during lockdown tended to feel significantly less energetic (p<.05) and friendly (p<.01). In addition, they recorded significantly lower scores in marital satisfaction with their peers (p<.05). The runners with a higher degree of dependence on physical exercise registered significantly higher levels of depression, tension and anger than non-dependent runners (p<.001). Runners whose partners were physically active and did not have children had significantly higher scores marital satisfaction than runners whose partners were not physically active and had children (p<0.05). These findings seem to indicate that the psychological approach to athletes in the context of crises such as the pandemic should consider not only individual aspects, but also include the family perspective.